PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN: (Studi Empiris Pada Perusahaan Sektor Properti dan real estate Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Tarisa Nopriani; Indah Rahayu Lestari (CV. Denasya Smart Publisher, 2024)
This study aims to determine the effect of Good Corporate Governance proxied by (Board of Directors, Independent Board of Commissioners, and Audit Committee), Capital Structure, and Company Size on Company Financial Performance. The population in this study were property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. The sample was determined using a purposive sampling technique with certain criteria and a sample of 53 companies was obtained. This study uses a multiple linear analysis method assisted by the SPSS Version 22 program. The results of this study indicate that the Board of Directors and Capital Structure have no effect on Financial Performance, while the Independent Board of Commissioners, Audit Committee, and Company Size have a positive and significant effect on Financial Performance.